Neutophil to Lymphocyte Ratio: A Marker for Preterm Labor? [21R]. (May 2017) - Lam, Melissa Chu; Hunt, Jonathan; Anasti, James
Abstract : INTRODUCTION: Investigators have postulated that preterm labor may result from inflammation. Neutrophil/lymphocyte ratio (N/L) has been used as marker to determine sub-clinical inflammation and prognosis in several system disorders. The N/L is easy to obtain and inexpensive, which would allow a widespread clinical use in the evaluation of patients. We therefore hypothesis that due to inflammation, preterm patients would have higher N/L ratio compared to term controls. METHODS: We randomly selected patients delivered before 37 weeks (PT) and patients that delivered at term (T) during the last 10 years. Only patients in active labor were included. We compared their N/L Ratio at the time of admission to Labor and Delivery. We excluded individuals with known infection, inflammatory diseases, and hematological disorders, as well all those that received steroids at least 3 weeks prior to determining their N/L ratio. RESULTS: We compared 137 PT (32.4 ± 4.1 wks) and 145 T (39.2 ± 1.1 wks) patients of similar age. They differed by gravity (PT 2.8 ± 1.9; T 2.0 ± 1.4, p= 0.001), and parity (PT 0.8 ± 1.1; T 1.2 ± 0.8, p=0.001). Preterm patients had higher rates of BMI greater than 35 (PT 13.8%; T 5.5%, p=0.3), tobacco use (PT 24%, T 11%, p=0.001) and hypothyroidism (PT 10.2%; T 2.7%, p=0.001). N/L ratio was significantly elevated in preterm patients compared to those delivered at term (PT 5.9 ± 5.1; T 4.7 ± 3.2, p=0.007). CONCLUSION: N/L ratio appears to be elevated in preterm delivery. The clinical utility warrants further study.